QUBIC VII: The feedhorn-switch system of the technological demonstrator - Cavaliere, F. (2021)
We present the design, manufacturing and performance of the horn-switch system developed for the technological demonstrator of QUBIC (the Q&U Bolometric Interferometer for Cosmology). This system consists of 64 back-to-back dual-band (150 GHz and 220 GHz) corrugated feed-horns interposed with mechanical switches used to select desired baselines during the instrument self-calibration. We manufactured the horns in aluminum platelets milled by photo-chemical etching and mechanically tightened with screws. The switches are based on steel blades that open and close the waveguide between the back-to-back horns and are operated by miniaturized electromagnets. The measured electromagnetic performance of the feedhorns agrees with simulations. In particular we obtained a return loss around -20 dB up to 230 GHz and beam patterns in agreement with single-mode simulations down to -30 dB. The switches for this prototype were designed and built for the 150 GHz band. In this frequency range we find return and insertion losses consistent with expectations (< -25 dB and ∼-0.1 dB, respectively) and an isolation larger than 70 dB. In this paper we also show the current development status of the feedhorn-switch system for the QUBIC full instrument, based on an array of 400 horn-switch assemblies.